Epidemiological burden of postmenopausal osteoporosis in the UK from 2010 to 2021: estimations from a disease model. - Gauthier, A; Kanis, J; Jiang, Y; Martin, M; Compston, J; Borgström, F; Cooper, C; McCloskey, E (2011)
UNLABELLED: This article describes the adaptation of a model estimating the burden of postmenopausal osteoporosis (PMO) to the UK. PURPOSE: The purpose of this study was to estimate the present and future epidemiology of PMO in the UK. METHODS: For each year of the study, the 'incident cohort' (women experiencing a first osteoporotic fracture) was identified and run through a Markov model using 1-year cycles until 2020. Health states were based on the number of fractures and death. Fracture by site was tracked for each health state. Transition probabilities reflected fracture site-specific risk of death and subsequent fractures. RESULTS: Assuming that the rate of incident fractures by age is constant over time, the model estimated the total number of PMO fractures at 224,219 in 2010, including 51,927 hip and 30,994 clinical vertebral fractures. These estimates were predicted to increase by 17.2%, 16.6% and 17.9%, respectively, by 2020. The number of postmenopausal women living with osteoporosis was predicted to increase from 1.8 million in 2010 to 2.1 million in 2020 (+16.5%). A sensitivity analysis demonstrated that the estimated number of fractures is most sensitive to the assumption made on the trends in the rate of incidence. CONCLUSION: The PMO disease model, first developed for Sweden, was adapted to the UK. Due to demographic changes, the burden of osteoporosis is expected to increase by almost a fifth by 2020. Due to the lack of country-specific data, these results rely on several assumptions regarding the incidence of non-hip fractures, trends in BMD and rate of incidence over time.